Co‐adsorption of Cations as the Cause of the Apparent pH Dependence of Hydrogen Adsorption on a Stepped Platinum Single‐Crystal Electrode - Chen, Xiaoting; McCrum, Ian T.; Schwarz, Kathleen A.; Janik, Michael J.; Koper, Marc T. M. (Angewandte Chemie International Edition, 2017)
The successful deployment of advanced energy‐conversion systems depends critically on our understanding of the fundamental interactions of the key adsorbed intermediates (hydrogen *H and hydroxyl *OH) at electrified metal–aqueous electrolyte interfaces. The effect of alkali metal cations (Li+, Na+, K+, Cs+) on the non‐Nernstian pH shift of the step‐related voltammetric peak of the Pt(553) electrode is investigated over a wide pH window (1 to 13) by means of experimental and computational methods. The co‐adsorbed alkali cations along the step weaken the OH adsorption at the step sites, causing a positive shift of the potential of the step‐related peak on Pt(553). Density functional calculations explain the observations on the identity and concentration of alkali cations on the non‐Nernstian pH shift, and demonstrate that cation–hydroxyl co‐adsorption causes the apparent pH dependence of “hydrogen” adsorption in the step sites of platinum electrodes. Keeping in step: A combination of experiment and computations shows that the apparent pH dependence of hydrogen adsorption in step and defect sites of platinum electrodes is due to the co‐adsorption of cations with hydroxyl. A model for this effect, which is of key importance for interpreting the electrocatalytic activity of platinum, is outlined.